DDIT4/mTOR signaling pathway mediates cantharidin-induced hepatotoxicity and cellular damage - Wenchao Tang; Yue Pan; Can Zhu; Didong Lou; Fang Peng; Qin Shi; Yuanyuan Xiao; Yuanyuan Xiao (Frontiers in Pharmacology)
BackgroundCantharidin (CTD) extracted from the traditional Chinese medicine Mylabris has significant therapeutic effects on various tumors. However, the high toxicity of CTD can cause serious liver damage, although the related molecular mechanisms remain unclear.MethodsIn this study, we established models of CTD-induced liver and L-O2 cell damage in mice in vivo and in vitro. Subsequently, liver function indicators were detected in mouse serum, while liver tissues were subjected to pathological and transmission electron microscopy observations. L-O2 cell activity was investigated using the CCK-8 assay, and the mRNA and protein expression of DNA damage-induced transcription factor 4 (DDIT4) in liver tissue and L-O2 cells was detected using qPCR, immunohistochemistry, and western blotting. Western blotting was also used to detect the expression levels of autophagy- and apoptosis-related proteins in liver tissue and L-O2 cells. After RNAi interference with DDIT4, Rap, and 3-MA treatment, autophagy and apoptosis of L-O2 cells were detected using western blotting, flow cytometry, transmission electron microscopy, and confocal microscopy.ResultsFollowing CTD exposure, the mouse liver showed significant pathological damage and an increase in autophagic lysosomes, while the vitality of L-O2 cells showed a significant decrease. CTD led to a significant increase in the mRNA and protein levels of DDIT4 in both liver tissue and L-O2 cells, as well as a significant increase in LC3-II, Beclin1, and Bax, whereas p-mTOR and Bcl-2 were significantly decreased. Following DDIT4 interference and 3-MA treatment, the levels of autophagy and apoptosis induced by CTD in L-O2 cells were reduced. After Rap treatment, both autophagy and apoptosis of CTD-induced L-O2 cells were significantly enhanced.ConclusionThe molecular mechanism of CTD-induced toxicity in mouse liver and L-O2 cells is mainly through DDIT4/mTOR signaling pathway activation, leading to an increase in autophagy and apoptosis levels.